March of nutrient absorption and growth of fertigated melon ‘Gladial®’ - Bagagim, João Batista Coelho; Araújo, Micaele Bagagi; Tavares Filho, Gilberto Saraiva; Sousa, José Sebastião Costa de; de Oliveira, Fabio Freire; Araújo, Cícero Antônio de Sousa (Comunicata Scientiae, 2022)
The use of fertigation in melon cultivation is becoming increasingly common, and there is a need to optimize the doses of applied fertilizers. Knowledge of the nutritional demands of the crop and its rate of uptake is essential for determining the amount of nutrients required at different phenological stages. The objective of this study was to determine the rate of macronutrient and micronutri ent uptake in fertigated melons, as well as the accumulation of fresh and dry matter in leaves, stems, and fruits. This study was performed in Petrolina-PE, in an entirely randomized experimental design with nine evaluation periods and six repetitions. Plants were collected at 7, 14, 21, 28, 36, 43, 50, 57, and 64 days after emergence (DAE). The accumulation of N, P, K, Ca, Mg, Fe, Mn, Zn, Cu, dry matter, and fresh matter in the leaves, stems, fruits, and total matter accumulation throughout the cycle was analyzed. Dry matter increases at 64 DAE. Nutrient accumulation was in the following order of micronutrients: K>Ca>N>Mg>P and Fe>Mn>Zn>Cu.